Imperfect Information of Bankers Clause in Credit Agreements in Banking Institutions: Further Legal Impact - Hamzah, Rosyidi; Adinda, Fadhel Arjuna; Hardiago, David; Woodward, John (Lex Scientia Law Review, 2023)
Banking institutions primarily serve as intermediaries, collecting funds from the public through deposits (including savings, deposits, and current accounts) and redirecting these funds to the public in the form of credit. The execution of credit transactions necessitates a formal credit agreement to ensure legal certainty. These agreements typically follow a standardized pattern, with the bank drafting the terms and customers, often in a position of economic dependency, obliged to sign. Within the credit agreement, a crucial component is the banker clause, designed to mitigate credit risks. In the event of unforeseen circumstances, such as the customer's demise, this clause ensures that an insurance company settles the remaining debt. However, the effectiveness of this clause is contingent on the comprehensiveness of the insurance coverage. One noteworthy issue arises from the lack of transparency during the signing of credit agreements. Customers, represented solely by the bank during this process, may not be fully informed about the intricacies of the banker clause. Consequently, customers have found themselves in situations where they are obligated to fulfill outstanding credit obligations despite insurance claim rejections due to undisclosed specifics of certain diseases. To address this concern, it is imperative to establish explicit regulations governing disclosing information related to the banker clause during the signing of the credit agreement. This necessitates a collaborative effort involving the customer, bank, and insurance institution, ensuring that all relevant parties convene to discuss and clarify the terms of the credit agreement, particularly those related to the banker clause.